تأثير جولات اللكم التنافسي المشروط على بعض الأداءات المهارية "الهجومية، الدفاعية" وعلاقتها باستراتيجية المواجهة واليقظة العقلية للملاكمين - جودة، أحمد محمد محمد كامل; محمد، محمد إبراهيم محمد (جامعة حلوان - كلية التربية الرياضية للبنين, 2022)
هدف البحث إلى استخدام جولات لكم مشروط ترتكز على تطوير الاداءات البدنية والمهارية الغير مستخدمة خلال المباريات والتعرف على تأثيرها على نسب الاداءات المهارية (الدفاعية والهجومية) وعلاقتها بمستوى استراتيجية المواجهة واليقظة العقلية لدى عينة البحث. تم استخدام المنهج التجريبي بالتصميم التجريبي وبلغت عينة البحث على (١٥) ملاكم يمثلوا نسبة مئوية (48.38%) من المجتمع الكلي للبحث، كما تم اختيار (١٢) لاعب يمثلون (38.70%) من داخل مجتمع البحث وخارج العينة الأساسية لإجراء الدراسة الاستطلاعية وكانت أهم أدوات البحث مقياس اليقظة العقلية، واستراتيجية المواجهة واليقظة العقلية وبعض الاختبارات البدنية ومستوى الأداء المهارى للملاكمين وكانت أهم النتائج أن جولات اللكم التنافسي أثرت إيجابيا في تحسين بعض المتغيرات البدنية قيد البحث بنسب تحسن مئوية تراوحت ما بين (7.23%: 43.335%)، وكذلك في تحسين بعض المتغيرات المهارية (الهجومية والدفاعية) قيد البحث بنسب تحسن مئوية تراوحت ما بين (36.59%: 96.92%) وتحسين بعض مستوى استراتيجية المواجهة بنسبة مئوية بلغت (21.545)، كما ارتفع مستوى اليقظة العقلية بنسبة مئوية بلغت (36.54%)، توجد علاقة ارتباطية طردية بين الاداءات المهارية (الهجومية والدفاعية) ومستوى استراتيجية المواجهة واليقظة العقلية قيد البحث. The aim of the research is to use conditional punch rounds based on the development of unused physical and skill performances during matches and to identify their impact on skill performance ratios (defensive and offensive) and their relationship to the level of confrontation strategy and mental alertness in the research sample. The experimental approach was used with the experimental design, and the research sample amounted to (15) boxers representing a percentage (48.38%) of the total research community, and (12) players representing (38.70%) were selected from within the research community and outside the basic sample to conduct the survey and it was the most important Research tools The mental alertness scale, confrontation strategy, mental alertness, some physical tests, and the level of skill performance for boxers. The most important results were that the competitive punching rounds positively affected the improvement of some of the physical variables under discussion with percentage improvement rates that ranged between (7.23%: 43.335%), as well as in improving some The skill variables (offensive and defensive) are under discussion with percentage improvement rates that ranged between 36.59%: 96.92% and improvement of some level of confrontation strategy by a percentage of (21.545), and the level of mental alertness increased by a percentage of (36.54%). There is a direct correlation between the skill performances (offensive and defensive), the level of confrontation strategy, and mental alertness under discussion.
Keywords: رياضة الملاكمة -- اللياقة البدنية -- المهارات الرياضية -- اللكم التنافسي